2018
DOI: 10.1007/s00406-018-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in resting-state gamma activity in patients with schizophrenia: a high-density EEG study

Abstract: Alterations of EEG gamma activity in schizophrenia have been reported during sensory and cognitive tasks, but it remains unclear whether changes are present in resting state. Our aim was to examine whether changes occur in resting state, and to delineate those brain regions where gamma activity is altered. Furthermore, we wanted to identify the associations between changes in gamma activity and psychopathological characteristics. We studied gamma activity (30-48 Hz) in 60 patients with schizophrenia and 76 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 86 publications
3
27
0
2
Order By: Relevance
“…54 In addition, abnormalities in resting state gamma and beta frequencies are known as a representative trait marker of SCZ. [55][56][57] Increases in theta and delta frequencies and reduced beta and gamma frequencies in SCZ are consistently observed. 58 Reduced high-frequency alpha activity could stem from the fact that the bandwidth of high-frequency alpha is close to the beta and gamma frequencies.…”
Section: Discussionmentioning
confidence: 84%
“…54 In addition, abnormalities in resting state gamma and beta frequencies are known as a representative trait marker of SCZ. [55][56][57] Increases in theta and delta frequencies and reduced beta and gamma frequencies in SCZ are consistently observed. 58 Reduced high-frequency alpha activity could stem from the fact that the bandwidth of high-frequency alpha is close to the beta and gamma frequencies.…”
Section: Discussionmentioning
confidence: 84%
“…A number of resting-state EEG studies have been conducted on patients with schizophrenia (vs. healthy controls) most often with eyes closed (although see Venables et al, 2009; Hanslmayr et al, 2013; Narayanan et al, 2014 for three eyes open studies). In total, 37 schizophrenia studies were identified for this review (Clementz et al, 1994; Sponheim et al, 1994; Wada et al, 1994; Omori et al, 1995; Pascual-Marqui et al, 1999; Begić et al, 2000; Harris et al, 2001; Knott et al, 2001a; Wuebben and Winterer, 2001; Mientus et al, 2002; Veiga et al, 2003; Kirino, 2004; Harris et al, 2006; Kirino, 2007; Knyazeva et al, 2008; Tislerova et al, 2008; John et al, 2009; Venables et al, 2009; Bandyopadhyaya et al, 2011; Begić et al, 2011; Itoh et al, 2011; Schug et al, 2011; Hong et al, 2012; Hanslmayr et al, 2013; Kam et al, 2013; Narayanan et al, 2014; Ranlund et al, 2014; Tikka et al, 2014; Andreou et al, 2015; Garakh et al, 2015; Goldstein et al, 2015; Kim et al, 2015; Mitra et al, 2015; Shreekantiah Umesh et al, 2016; Mitra et al, 2017; Moeini et al, 2017; Baradits et al, 2018). The median sample size was 63 (range 26–425), with the average age of participants being 31 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, gamma-band power was not reported. While some studies showed increased resting-state gamma-band power in schizophrenia in eyes-closed condition (18)(19)(20), Grent-'t-Jong et al (21) found an increased gamma power (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) at the occipital cortex and a decreased at the prefrontal cortex in first episode schizophrenia patients (N = 21) and showed a decreased MEG gamma power at the frontal, temporal, and sensorimotor cortices in chronic schizophrenia patients (N = 34) compared to healthy controls (N = 37).…”
Section: Introductionmentioning
confidence: 99%